2021
DOI: 10.1007/s10049-020-00832-2
|View full text |Cite|
|
Sign up to set email alerts
|

Which health-related reasons lead to prehospital emergency care and how does subjective emergency status connect to subsequent care?

Abstract: Objectives/Background In many countries, the use of emergency medical services (EMS) increases steadily each year. At the same time, the percentage of life-threatening complaints decreases. To redesign the system, an assessment and consideration of the patients’ perspectives is helpful. Methods We conducted a paper-based survey of German EMS patients who had at least one case of prehospital emergency care in 2016. Four health insurance companies sent out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…It remains contradictory that 89 % of all respondents confirmed an emergency as a reason while 26 % worried to become an emergency soon. The percentage (84 %) of people answering that someone else's call was reason for the EMS use seems plausible in combination with the high amount of third party calling in their index case (89 %) reported in a previous paper [33]. As it is very likely that not every patient had relevant impairments and only 17 % reported unconsciousness, one may assume that the patients' wish had at least some impact on third party calling.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It remains contradictory that 89 % of all respondents confirmed an emergency as a reason while 26 % worried to become an emergency soon. The percentage (84 %) of people answering that someone else's call was reason for the EMS use seems plausible in combination with the high amount of third party calling in their index case (89 %) reported in a previous paper [33]. As it is very likely that not every patient had relevant impairments and only 17 % reported unconsciousness, one may assume that the patients' wish had at least some impact on third party calling.…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, they overrepresented southern federal states and patients with statutory health insurance, lacking those with private insurance (which equal about 11 % of all persons insured in Germany [39]). According to results published in a previous paper [33], there is a high plausibility that the vast majority of the respondents were able to recall their EMS use, even though it took place two years ago: For example, self-reported complaints versus diagnosed ICD codes (during inpatient care accompanying the EMS use) correspond well. Patients also reported that their EMS use was a rare event (median/modus: 2 EMS uses per life).…”
Section: Limitationsmentioning
confidence: 90%
“…Reaching risk-groups by addressing them or their relatives directly: Previous findings demonstrate that the most likely person to call an ambulance for someone else in case of a perceived emergency is a family member [ 21 ]. Additionally, a high proportion of patients receiving long-term care have an increased sepsis risk because of older age or underlying diseases, and the majority of long-term care is provided at home by relatives, not in nursing homes [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Einen Teil der steigenden Einsatzzahlen machen Einsätze aus, welche ursprünglich keine oder eine geringe rettungsdienstliche Relevanz haben. Die Ursachen hierfür sind multifaktoriell und wissenschaftlich noch nicht in Gänze erforscht [18,25]…”
unclassified